2021
DOI: 10.1073/pnas.2100171118
|View full text |Cite
|
Sign up to set email alerts
|

Proton-gated coincidence detection is a common feature of GPCR signaling

Abstract: The evolutionary expansion of G protein-coupled receptors (GPCRs) has produced a rich diversity of transmembrane sensors for many physical and chemical signals. In humans alone, over 800 GPCRs detect stimuli such as light, hormones, and metabolites to guide cellular decision-making primarily using intracellular G protein signaling networks. This diversity is further enriched by GPCRs that function as molecular sensors capable of discerning multiple inputs to transduce cues encoded in complex, context-dependent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…In summary, all three GPCRs can signal via different Gα subunits and coupling may occur in a cell-specific manner. Moreover, the sensitivity to pH may also dependent on the Gα subunit associated to the respective GPCR [52] (Fig. 1).…”
Section: Gpr4mentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, all three GPCRs can signal via different Gα subunits and coupling may occur in a cell-specific manner. Moreover, the sensitivity to pH may also dependent on the Gα subunit associated to the respective GPCR [52] (Fig. 1).…”
Section: Gpr4mentioning
confidence: 99%
“…It should be also noted that multiple other GPCRs may be modulated positively or negatively by protons and GPCRs other than those covered in this review may also function as protons sensors. For example, Kopolka et al demonstrated that the adenosine A2a receptor can be activated solely by H + [52]. Also, the affinity of the calcium-sensing receptor (CaSR) to calcium is modulated by extracellular protons [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, it deserves to be mentioned that the general acidification spent medium from cultivated yeast is an important parameter to consider when establishing and optimizing biosensing workflows, especially when using GPCRs with proton-gated coincidence detection such as 5-HT4. 51 Indeed, we observed a general lowering of the pH with increasing ratio of the spent medium added to the medium with the sensor ( Supporting Information Figure S5).…”
Section: Resultsmentioning
confidence: 83%
“…As pH has recently been shown to drastically modulate the signalling of human G protein-coupled receptors in yeast, we first assessed the dose-response of the CB2 biosensor to THC over a range of physiologically relevant conditions 37 (Supplementary Fig. 5a ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in this work, not all mammalian GPCRs functionally express in yeast, and those that have been previously reported may not work in other settings without the original knowhow. Work is needed to uncover more universal principles for improving the expression, localisation, and coupling of GPCRs in yeast, but progress towards this is underway 37 , 39 .…”
Section: Discussionmentioning
confidence: 99%